El cuidado de sí en salud en adultos jóvenes (2007)
ABSTRACT: The article synthesizes an investigation on the social representations of the self care health in a group of adult men young college students of the city of Medellín. One was that their processes of socialization and the life experience cross and determine guidelines of well-taken care of health. They identify this care with the personal safety, the sexuality responsible and the prevention for risks for the health, and for that reason they develop actions that contribute to diminish the possibility of becoming ill. Also an evident tendency of the young adult men is observed to naturalize practices of “oversight” that imply for the person risks as the extreme sports, the alcohol consumption and the tobacco abuse. In agreement with the findings, the author recommends to create public policies destined to this population sector, to foment daily actions that harness the self care in health.